FREQUENCY OF ANXIETY AND PSYCHOSOCIAL STRESSFUL EVENTS IN PATIENTS WITH ACUTE MYOCARDIAL INFRACTION - Khan, Mohammad Asghar; Karamat, Mehwish; Hafizullah, Mohammad; Nazar, Zahid; Fahim, Muhammad; Gul, Adnan Mehmood (Journal of Ayub Medical College Abbottabad, 2010)
Background: The impact of psychological factors in acute coronary events is only now emerging. A growing body of evidence attests to the influence of emotional and stress-related psychosocial factors in the aetiology of Coronary Artery Disease (CAD) and morbidity and mortality among individuals with coronary heart disease. The objectives were to look for the frequency of anxiety and psychosocial stressful events in patients with acute myocardial infarction. Methods: Two hundred consecutive patients of Acute Myocardial Infarction (AMI) without complications who presented to the Coronary Care Unit of Cardiology Department, Lady Reading Hospital Peshawar, and 200 healthy controls among relatives of patients were assessed on Holmes Rahe Social scale (HRS) and Hospital Anxiety and Depression Scale (HADS) scale for the presence of anxiety and stressful life events in period preceding AMI. Results: Sixty-three percent of the patients were male in both groups. Mean age of patients was 59 years while that of controls was 52 years. For scores of anxiety on HADS, 34% of the controls had normal score compared to of the 19% AMI group (p<0.001), while 57% of the AMI patients had abnormal score compared to 39% of the control group (p<0.001). The number events reported on HRS scale in patients with AMI were significantly more (4.2±2) compared to the number of events (2.7±1.6) in the control group with (p<0.001). Scores for the number of events on HRS scale were significantly less (98±64) in controls compared to (158±5.8) in group with AMI (p<0.001). Anxiety was diagnosed in 70% of the female patients compared to 50% of the male patients. Conclusion: Significant number of patients with acute myocardial infarction when assessed on standard scales had anxiety and stressful life events in the weeks preceding the event. These were more common in female than male patients. Keywords: Anxiety, Stress, Myocardial Infarction, Coronary, HADS